2018
DOI: 10.3233/jbr-180312
|View full text |Cite
|
Sign up to set email alerts
|

Andean Berry (Vaccinium meridionale Swartz) Juice improves plasma antioxidant capacity and IL-6 levels in healthy people with dietary risk factors for colorectal cancer

Abstract: En primer lugar, a la Universidad Nacional de Colombia, por ser una magnifica institución de educación superior; permitiéndome formarme en áreas de la agricultura, el desarrollo rural y la docencia; a la Facultad de Ciencias Agrarias, mi segundo hogar, dónde me he formado profesionalmente; al CIER, por el apoyo económico para la fase de campo del presente trabajo.Al profesor Yesid Aranda por su dedicación y tiempo empleado en cada asesoría, de quién aprendí acerca de la constancia y la honestidad; así como, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 74 publications
0
4
0
1
Order By: Relevance
“…In that sense, both ellagitannins and green tea flavan-3-ols are catabolized by the gut microbiota, of which the main bioavailable products are Colorectal cancer has been recorded as one of the common cancer types, which is the second most frequently diagnosed cancer in women and the third in men (Agudelo, Ceballos, Gómez-García, & Maldonado-Celis, 2018). The effect of black raspberry intervention (10% black raspberry in diet) on the intestinal tumor-bearing mice has been investigated by May, McDermott, Marchesi, and Parry (2020).…”
Section: Cancermentioning
confidence: 99%
“…In that sense, both ellagitannins and green tea flavan-3-ols are catabolized by the gut microbiota, of which the main bioavailable products are Colorectal cancer has been recorded as one of the common cancer types, which is the second most frequently diagnosed cancer in women and the third in men (Agudelo, Ceballos, Gómez-García, & Maldonado-Celis, 2018). The effect of black raspberry intervention (10% black raspberry in diet) on the intestinal tumor-bearing mice has been investigated by May, McDermott, Marchesi, and Parry (2020).…”
Section: Cancermentioning
confidence: 99%
“…(2017) informed about the reducing effect of ABJ on the GSH/GSSG ratio on SW480 cells, associated with an oxidative stress‐induced pro‐apoptotic effect. Moreover the antioxidant potential of ABJ was previously examined by our research group in a clinical study involving healthy men and women (18–60 years) with dietary factors for colorectal cancer (Agudelo, Ceballos, et al., 2018). In this study, ABJ consumption (250 ml for 14 days) showed increased plasmatic antioxidant capacity ( p > .01) and significant 8‐isoprostane reductions ( p < .01), compared to the basal state of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo, existe un comercio incipiente para los frutos de Macleania rupestris (Kunth) A.C.Sm., una especie ampliamente reconocida en la ruralidad de la Sabana de Bogotá y en otras regiones del país (Lagos-Burbano et al, 2010;Ortiz et al, 2021). El interés en Colombia por los frutos de las ericáceas ha crecido de gran manera debido al potencial que ofrecen algunas especies para el desarrollo de sistemas productivos en la región Andina, así como por sus propiedades antioxidantes, medicinales y nutricionales (Cardozo et al, 2009;Ligarreto, 2009;Lopera et al, 2013;González et al, 2017;Agudelo et al, 2018;Ortiz et al, 2021;Gil et al, 2022). Aunque a nivel del Neotrópico la especie más reconocida es Vaccinium floribundum (Luteyn y Pedraza-Peñalosa, 2021), en Colombia los mayores esfuerzos en investigación y desarrollo de un frutal nativo de Ericaceae se han centrado en Vaccinum meridionale (Ligarreto, 2009).…”
Section: Introductionunclassified